Modelling impacts of lateral N flows and seasonal warming on an arctic footslope ecosystem N budget and N2O emissions based on species-level responses - Wenxin Zhang (4038902) (2021)
These datasets support the article which is under the review in the journal "Biogeochemistry". The datasets include the model accepted runs and four scenario runs. The readers should use CoupModel (www.coupmodel.com) to open the file and browse the data.